SCALE UP The Production Results and Income of the Bina Sukses Jejama Cooperative by utilizing Renewable Technology - Suaidah, Suaidah; Putri, Novia Utami; Yusup, Maulid Wahid (International Journal of Public Devotion, 2024)
Koperasi Bina Sukses Jejama is a cooperative body which operates in the field of freshwater fish cultivation. The partner business location is on Jl. Raya Sukawangi, Sukawangi village, Performance subdistrict, Pringsewu district. Koperasi Bina Sukses Jejama has a driving force named Hidayat Septa Kesuma. Koperasi Bina Sukses Jejama has been established since 2020 and currently has 7 fish breeder members with several types of fish, namely tilapia, goldfish and catfish. The problem is with partners: 1) Losses from production results, such as less than optimal production results or many fish dying, caused by changes in temperature and pH of fish pond water; 2) Partners do not yet have a control system for basic freshwater fish components that can monitor the temperature and acidity or pH of the water in the pond; 3) Partners do not yet have an independent source of electrical energy to supply production; 4)Partners always feels disadvantaged because the harvest is always played with by the fish collectors in the village; 5) There are very few fish collectors in Sukawangi village so they cannot accommodate all the harvest from the fish farmers to be sold on the market. Based on the priority problems faced by partners, the solutions offered by the proposing team for this PKM scheme are: 1) Applying a solar panel based water temperature and pH level sensor; 2) Implement digital marketing applications; 3) Assistance and training in the use of tools and applications.The result of this service is an increase in fish harvest from the previous 1-2 tons in 3-4 months to 2.5 tons. Evaluation results from digital marketing application training activities also show that 83% of Bina Sukses Jejama Cooperative members' knowledge and understanding has increased in terms of using digital marketing applications